To have money is to have freedom. On the bad luck of being poor and other inequalities, from Gerald A. Cohen - Ribotta, Silvina (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2024)
Gerald Cohen has made a genuinely egalitarian imprint on the debates on justice, which demands to be analysed in order to properly understand the challenges facing social justice in the world. From his critical acuity and the framework of analytical Marxism that have made him one of the most brilliant contemporary philosophers, he has defended a particular egalitarianism of luck that shields the demand to compensate for the impacts of brute luck and reinforces arguments about the reconsideration of responsibility andchoice that define optional luck –at first, non-compensable–. Moreover, from the conditioning unequal in which people develop their lives and make their life choices and how these impact on how free and responsible (or not) they turn out to be. Cohen offers his proposal of equality in access to social advantages from a complex theoretical and analytical framework on incentives, market conditioning, and the consideration of expensive tastes, the impact of inequalities, and the demands of equal opportunities. Therefore, he warns that poverty implies, from his acute criticism of the contemporary political andeconomic system, deprivations to the way in which we exercise our freedoms
Keywords: equality; freedom; egalitarianism of luck; inequality; equal opportunities; poverty